Gender Sensitivity of Teacher Education Curricula in the Republic of Croatia - Rogošić Silvia; Baranović Branislava (De Gruyter, 2024)
The research aims to determine whether and to what extent teacher education curricula in Croatia are gender sensitive and to examine the status of courses dealing with gender-related topics. For this purpose, a qualitative and quantitative analysis of the seven teacher education curricula was conducted. The analysis was based on Bernstein's theory of classification and framing rules, which explains how control and power over knowledge and curriculum are exercised by selecting knowledge (from scientific disciplines) for the curriculum, design rules, and curriculum implementation. The findings indicate that gender-based knowledge is not given high status and significance as a teaching subject. Gender-related topics are included in teacher education curricula by weak framing and classification rules. While there are several advantages to such a curriculum design, weak classification and framing rules can lead to a lack of compliance in education on gender-related topics. A vague structure can interfere with students' understanding of basic concepts and their interconnectedness. Students can choose courses based on personal interest rather than necessity and importance. Recommendations are made to achieve a higher level of gender sensitivity in teacher education curricula, which would contribute to better preparation of teachers for the education of children on gender equality.